Chao: a framework for the development of orchestration technologies for technology-enhanced learning activities using tablets in classrooms. (2018) - Wang, Patrick; Tchounikine, Pierre; Quignard, Matthieu
In technology-enhanced learning, orchestration technologies refer to computer systems that support teachers in the orchestration of learning applications. Due to the specificity and diversity of each learning application, the use of these orchestration technologies is often not adequate in situations that they were not designed for in the first place. In this article, we tackle this issue and present the software framework Chao. This framework has been designed to provide a set of classes, methods, and user interfaces to facilitate the development of orchestration technologies for tablets. The evaluation of this framework concerns its design, the usability of its user interfaces, and its ability to be adapted for various learning applications. The results suggest that teachers found the instances of the framework useful in assisting them during their orchestration tasks, and that little work is required to instantiate the framework.